Characterization of site‐specific vegetation activity in Alaskan wet and dry tundra as related to climate and soil state. Issue 2 (8th February 2022) - Brown, Michael Gregory; McDonald, Kyle C.; Zimmermann, Reiner; Steiner, Nicholas; DeVries, Stephanie; Bourgeau‐Chavez, Laura
Abstract: We present discrete (2‐h resolution) multi‐year (2008–2017) in situ measurements of seasonal vegetation growth and soil biophysical properties from two sites on Alaska's North Slope, USA, representing dry and wet sedge tundra. We examine measurements of vertical active soil layer temperature and soil moisture profiles (freeze/thaw status), woody shrub vegetation physiological activity, and meteorological site data to assess interrelationships within (and between) these two study sites. Vegetation phenophases (cold de‐hardening start, physiological function start, stem growth start, stem growth end, physiological function end, cold hardening completion) were found to have greater interannual day of year (DOY) occurrence variability at the dry site compared with the wet site. At the dry site, vegetation activity begins on average 7 days earlier and ends 11 days earlier. The mean active stem growth window lasts 54 days for the dry site and 51 days for the wet site. Vegetation, in both tundra environments, began cold de‐hardening functions (warm season prep) prior to atmospheric temperatures warming above 0°C. Similar results were found related to the critical soil freeze/thaw/transition dates; the dry site had a DOY phenophase occurrence range that was 8 days larger than that of the wet site. A longer continuous summer thaw period was captured at the wet site by 26 days throughout the active layer. In addition, the dry site was measured to have longer spring and fall soil isothermal conditions than the wet site by 9 and 5 days throughout the active layer. These results show that the dry site's willow shrub vegetation physiology and soil condition phenology is more variable than the wet site. Alongside the in situ data, a remote sensing product from NASA's MEaSUREs program was utilized; our research indicates that the AMSR‐derived satellite product is more precise over the wet tundra site with critical date alignment between remote sensing observations and in situ measurements ranging from 4 to 11 days. Furthermore, the AMSR product was shown to preemptively estimate land surface condition change during the spring transition for both tundra types while lagging during the fall transition and freeze‐up periods.